UJI AKTIVITAS EKSTRAK DAUN PIRDOT (Saurauia vulcani Korth) TERHADAP PERTUMBUHAN BAKTERI Bacillus subtilis - Ulfayani Mayasari (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
Pirdot is a plant that has been widely used by people to treat various diseases. Pirdot leaves extract contain of flavonoids which have antibacterial Substances. This research has a purpose to determine the activity of pirdot leaves extract (Saurauia vulcani Korth.) inhibit toÂ  bacterium Bacillus subtilis. This research uses an experimental method that are the maceration extraction method and testing the antibacterial activity by agar diffusion method. Result of the research was found that the inhibition area of pirdot leaves extract against Bacillus subtilis bacteria that have some clear zoneÂ  were 8.66 mm, 9.43 mm, 9.90 mm, 10.97 mm and 11.66 mm. Pirdot leaves can inhibit the growth of Bacillus subtilis bacteria.Keywords: Pirdot leaf, Bacillus subtilis, antibacterial.